Diet, physical activity, and obesity among ART-experienced people with HIV in South Africa. Issue 1 (2nd January 2023) - Hyle, Emily P.; Martey, Emily B.; Bekker, Linda-Gail; Xu, Ai; Parker, Robert A.; Walensky, Rochelle P.; Middelkoop, Keren
ABSTRACT: The prevalence of non-communicable diseases (NCDs) is increasing in South Africa, in part due to poor nutrition, physical inactivity, and obesity. We characterized the habits and understanding of diet, exercise, and obesity among people with HIV (PWH) taking antiretroviral therapy (ART). We conducted a cross-sectional study of ART-experienced PWH attending an HIV community health center near Cape Town, South Africa. We included PWH currently prescribed ART, older than 21y, and not pregnant. We collected demographic and clinical information and interviewed participants regarding their behaviors and knowledge related to diet, physical activity, and obesity. From March 2015 – February 2016, we enrolled 458 participants. Self-reported diets were low in nutritional diversity: 202 reported eating only starch and protein without vegetable/fruit in the prior 24 h. Although most participants (96%) acknowledged that exercise had health benefits, only 215 participants engaged in daily 30-minute walking or exercise. One quarter of participants recognized nocontributors to obesity, and almost 20% identified no health problems associated with obesity. Participants had diets low in nutritional diversity, modest exercise habits, and limited understanding of the impact of obesity on health. Further understanding of barriers to improving diet and exercise and reducing obesity are essential, especially as PWH age.